2006
DOI: 10.1002/jbm.a.30625
|View full text |Cite
|
Sign up to set email alerts
|

Determination of strength and deformation behavior of human cartilage for the definition of significant parameters

Abstract: In reconstructive surgery, an artificial supporting scaffold made from autogenous cartilage from the rib, the ear concha, or the nasal septum is used as a substitute for the destroyed endogenous tissue in the ear concha, the nose, the trachea, and in parts of the facial skeleton. For the successful use of polymer materials in reconstructive surgery, an exact knowledge of the material properties of the natural tissues is required. The applicability of conventional material test methods was examined with regard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 3 publications
0
42
1
Order By: Relevance
“…By performing modal analysis on the 3D FE head -neck system using the Willinger et al (1999). c Grellmann et al (2006). d Al-Bsharat (2000).…”
Section: Resultsmentioning
confidence: 99%
“…By performing modal analysis on the 3D FE head -neck system using the Willinger et al (1999). c Grellmann et al (2006). d Al-Bsharat (2000).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, in this study the concha was found to demonstrate a greater Young’s Elastic Modulus in compression to the helix. Grellmann et al designed a study to test nasal, costal and auricular cartilage using the following tests: micro-hardness, tension test, compression test, bending test 4. However, deeming the auricular cartilage too difficult to test, the authors did not calculate any numerical values for the auricular cartilages 4.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, estimates of elastic moduli for nasal cartilage presented in the literature vary greatly among studies and testing methods. Values for the elastic modulus of human septal cartilage presented in previous studies 11,12 have ranged from approximately 0.5 to greater than 30 MPa. Similarly, values for the elastic modulus of human LLC have ranged from 2 to 25 MPa.…”
Section: Discussionmentioning
confidence: 96%
“…The set of phantoms was created to have elastic moduli that spanned a range of values consistent with elastic moduli values for nasal cartilage calculated in previous studies (Table). 1115 The elastic modulus for the medial and lateral ends of all phantoms was 30.6 MPa.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation